The Effect of Educational Level and Work Experience on Employee Performance at the Garuda Ngamprah Chips Fac-tory in West Bandung (MSME) - Ayi Muhiban; Vira Puspita Dewi (Brilliant International Journal Of Management And Tourism, 2026)
This research was conducted on employees of the Garuda Cracker Factory MSME located on Jl. Raya Gadobangkong, West Bandung Regency exactly in Ngamprah District,. The research was done on purpose to identify the significance of the effect of education and also work experience, both separately and together. The methods applied were descriptive and associative. The analysis focus is individuals who are employees of the Garuda Cracker Factory MSME on Jl. Raya Gadobangkong, Ngamprah District, West Bandung West Bandung. The sample size used was 95 respondents. It applied a saturated sampling method because all population members were taken as samples, namely all employees at the Garuda Cracker Factory MSME. Then it applied analysis of multiple linear regression and also tests were done for the validity and also reliability of the instruments. The results show a significant influence on the variables in both individually and also collectively. The influence of education on performance reached 20.6%, while work experience influenced employee performance by 44.9%, and the combined influence of education and also work experience toward employee performance was 65.5%.